2016
DOI: 10.1016/j.marstruc.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the dynamic responses of a free-hanging water intake riser under vessel motion

Abstract: a b s t r a c tA large-scale model test of a free-hanging water intake riser (WIR) is performed in an ocean basin to investigate the riser responses under vessel motion. Top end of the WIR is forced to oscillate at given vessel motion trajectories. Fiber Brag Grating (FBG) strain sensors are used to measure the WIR dynamic responses. Experimental results firstly confirms that the free-hanging WIR would experience out-of-plane vortex-induced vibrations (VIVs) under pure vessel motion even for the case with a KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…Similar experiments with the steel catenary riser are conducted by Cunff et al (2005) and Pereira et al (2013) [31,32]. Moreover, the experiment of a free-hanging riser under vessel motion was also carried out [33,34]. VMI-VIV has also been observed.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar experiments with the steel catenary riser are conducted by Cunff et al (2005) and Pereira et al (2013) [31,32]. Moreover, the experiment of a free-hanging riser under vessel motion was also carried out [33,34]. VMI-VIV has also been observed.…”
Section: Introductionsupporting
confidence: 52%
“…The aforementioned relationship was first introduced to investigate the St number of a smooth rigid cylinder in an oscillatory flow by Sumer and Fredsøe (1988) [37]. However, it can be also applied for the flexible pipe and has been used in the SCR and free-hanging riser model tests [27,33,34]. Through Equation (18), the dominant frequency of all cases is first summarized, and the vortices shedding pairs N are then calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Fan et al [15] pointed out that the platform surge had a great influence on the hang-off drilling riser, especially resulted in the larger displacement and stress on the bottom of the riser. Wang et al [16] and Yin et al [17] performed experiments in towing tank for TTR which was excited at the top by platform surge motion, and the results showed that the platform surge had a great influence on VIV of TTR. e platform heave motion was applied as a moving boundary condition at the top of the riser.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the displacement of the riser was multiple times larger than that of the case without moving top-end. Wang et al and Yin et al [15,16] performed experiments in towing tank for the riser which was excited at the top by platform surge motion, and the results showed that the platform surge had a great influence on VIV of the riser. Drilling and production risers are mostly affected by VIV, which leads to increases in their hydrodynamic loading and reduction in their service life due to fatigue.…”
Section: Introductionmentioning
confidence: 99%